Production and characterization of chitosan from shrimp shells - Lim, Beng Seng (2013)
Chitosan is versatile natural polysaccharides which produce from ieacetylation of chitin. Chitin is the second most abundant natural biopolymer. It is a b.omo-biopolymer composed of P-1,4-N-acetylglucosamine and usually can be found in shell of crustaceans and the cell walls of fungi. Nowadays, seafood processing industry generates large amount of wastes, dumping these wastes into landfills and will create environmental problem such as water pollution and soil pollution. Current work is to produce and characterize chitosan from these shrimp shells wastes. Optimization of the chitosan production also was focused. Chitosan was produced throughout several steps which were deproteination and demineralization of shrimp shells and lastly deacetylation. Different NaOH concentration and different reaction time in deproteination step were carried out for optimization. The optimization for reaction time for deproteination was carried out based on the optimum NaOH concentration determined. After that, the characterization of chitosan was done in aspect moisture content, ash content and the yield. Sample with 10%NaOH with 3hours deproteination time gave highest yield of 13.10%. FTIR test was carried to was used to investigate the presented of amine and alcohol group in the chitosan. Most of the chitosan sample gave characteristic band ofNH2 at range 3450-3500cm-1 and hydroxyl group at range 1000-11 OOcm-1 • Thermal tests like thermogravimetric analysis (TGA) test was carried out to evaluate the thermal stability of composites. It was found that the most thermal stability of chitosan was 10% NaOH with 3hours. Synthesized chitosan was also used in treatment of waste water to remove the heavy metal. The highest efficiency of heavy metal removal subjected to chitosan with 10% NaOH with 3hours which remove 97.39% of iron,(Fe3+), 92.16% of copper(Cu2+), 72.21% of chromium (Cr2l and 52.72% of lead (Pb2l in lOOml of lOppm solution. Thus, it could be conclude that 10% NaOH with 3hours deproteination was optimum condition in production of chitosan.